Correlations between the cerebrospinal fluid surface tension value and 1. Concentration of total proteins 2. Number of cell elements - Kratochvíl, A; Hrncír, E (General physiology and biophysics, 2002)
The contribution gives a survey about the problematics of surface tension in biomedical sciences. The paper presents results of a study devoted to the cerebrospinal fluid. The distribution of the surface tension values of this liquid in healthy individuals is presented (n = 33), and further, statistically significant correlations between the cerebrospinal fluid surface tension value and 1. concentration of total proteins expressed by Spearman's coefficient p(s) = (-0.995) and 2. number of cell elements expressed through Spearman's coefficient p(s) = (-0.965) in cerebrospinal fluid are described.
Keywords: Blood Cells; senioři; statistika jako téma; Surface Tension; proteiny v mozkomíšním moku; Glucose; glukosa; povrchové napětí; Statistics as Topic; mozkomíšní mok; Middle Aged; Sensitivity and Specificity; mužské pohlaví; Adult; počet buněk; ženské pohlaví; Humans; Cerebrospinal Fluid; lidé středního věku; senzitivita a specificita; Cerebrospinal Fluid Proteins; dospělí; Cell Count; Female; Aged; krevní buňky; lidé; Male